Properties of self-compacting concrete incorporating palm oil fuel ash - Ehsan, Abdul Haq (2014)
Self-compacting concrete (SCC) is a concrete which can be placed and compacted under its self-weight with little or no vibration effort, and is at the same time, cohesive enough to be handled without segregation or bleeding. SCC is used to facilitate and ensure proper filling and good structural performance of restricted areas and heavily reinforced structural members. SCC is a flowing concrete with high workability. To achieve flowing concrete low volume of coarse aggregates is used, but the reduction in volume of coarse aggregates require high volume of paste, i.e. cement and fine aggregates, and use of super-plasticizers. Increased volume of cement and addition of super-plasticizer leads to higher cost. The cost of cement can be reduced by using supplementary cementitious materials. One of the potential recycle materials from palm oil industry is palm oil fuel ash (POFA). Palm oil is extracted from the fruit and copra of the palm oil tree. Self-Compacting concrete using POFA has been one of the researching focuses in Malaysia. This study outlines laboratory tests conducted for fresh and hardened properties of SCC incorporating POFA. This study determines the feasibility of replacing cement in SCC with POFA in percentages of 0%, 30% and 60% by weight of cement, with water/binder ratios of 0.40, 0.45 and 0.50. The fresh properties of SCC were tested for filling ability, passing ability and segregation resistance. Slump-flow and Orimet flow time tests were conducted for filling ability, J-ring and L-box tests for passing ability and V-funnel at T5minute for segregation resistance. The hardened properties like compressive strength, split tensile strength, flexural strength and Ultrasonic pulse velocity were determined. Test specimens comprising of cube, cylinder and beams were prepared and tested at 1, 7 and 28 days of curing. The results and observations revealed that high volume POFA can be utilized in the development of SCC in terms of flow and strength gain.